Continuous Flow Synthesis of Anisotropic Cadmium Selenide and Zinc Selenide Nanoparticles. Issue 3 (23rd January 2017) - Kumar, Vivek; Fustér, Héctor A.; Oh, Nuri; Zhai, You; Deshpande, Kishori; Shim, Moonsub; Kenis, Paul J. A.
Abstract: Anisotropic semiconductor nanoparticles find use in various applications ranging from electronics to photocatalysis and biolabeling. Batch synthesis methods typically used for their synthesis are often hampered by slow mixing, slow heating/cooling, and lack of batch‐to‐batch reproducibility, especially when scaling up. The modular continuous flow reactor reported here overcomes some of these challenges. It enables air‐sensitive syntheses at temperatures as high as 750 °C, supports rapid heating and cooling times (≈1 s or less), and enables syntheses that involve reagents that are viscous or even solid at room temperature. For validation we pursued two systems: the synthesis of (i) CdSe nanorods and bipods, and of (ii) ZnSe nanorods. Nanoparticles with low variance in quantum confined dimension (width) −16 % for CdSe and 11 % for ZnSe were obtained. For comparison, the same products were also synthesized using two batch approaches, hot‐injection and heat‐up, under similar conditions. The batch products were less uniform: 30 % variance in quantum confined dimension. Furthermore, the lack of precise temperature control in the batch processes resulted in CdSe nanorods with irregular‐shaped, jagged branches whereas the continuous process produced CdSe nanorods with uniform, straight branches. The modular continuous flow reactor design is suited for scale up, allowing working flow rates as high as ≈10 mL min −1, which translates into a production rate of ≈158 g day −1 for CdSe. Abstract : Keep it flowing : The reported stainless steel continuous flow reactor provides improved control over reaction conditions (temperature, residence time, reactant concentration) enabling the synthesis of anisotropic semiconductor nanoparticles with narrower size distribution.